(1021) The Methodology of Input – output Tables منهجية جداول المدخلات والمخرجات - Fathi El-Husseini Khalil. (INP, 2024)
The study explores various economic aspects by focusing on several key areas. It begins with an introduction highlighting the subject and its importance, followed by a discussion on the classification and aggregation of economic activities to provide a comprehensive view of different sectors. The study emphasizes the valuation of transactions, considering both net and gross sector outputs. It also examines the role of foreign trade and its significance to the economy. The concept of substitution in input-output tables and its impact on productivity is analyzed. Additionally, the study discusses the role of secondary products in economic activities and evaluates the effect of taxes on various economic processes.